Yes, it's true: Benign hysterectomy trends for gynecologic oncologists in the United States from 2015 to 2021 - Holtzman, Sharonne; Gellman, Caroline; Kaplowitz, Elianna; Barber, Emma; Huh, Warner; Blank, Stephanie V. (Gynecologic oncology, 2024)
The objective of this study was to determine the trends in benign surgery in GO practice across the United States. This was a retrospective cohort analysis of the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database from 2015 to 2021. Subjects were selected by filtering for cases of hysterectomy using current procedural terminology (CPT codes). Trends over time were assessed using linear regression for continuous outcomes and logistic regression for categorical outcomes. From the 2015 to 2021, the dataset contained 246,743 hysterectomies that were performed across the United States. For all gynecologic specialties, 188,534 (76%) were performed for benign indications and 59,209 (24%) were gynecologic cancer cases. The proportion of hysterectomies done by all specialists for benign indications increased with increasing year. When looking at hysterectomy cases by surgeon's subspecialty, GOs performed 35,680 (23%) of all benign cases over the entire time period. Over our study time period, the proportion of benign hysterectomies performed by GOs increased with increasing year with the proportion of benign hysterectomies done by GO in 2016 was 37.8% and reached 45.2% in 202. The proportion of hysterectomies done by all sub-specialists for cancer indications decreased with increasing year including the proportion of cancer cases performed by GOs for cancer indications. The proportion of benign hysterectomies performed by GO consistently increased every year. This study corroborates existing survey data and hypothesizes that the practice of GO is increasingly being consumed by general gynecology. •The proportion of benign hysterectomies performed by GO consistently increased every year from 2015 to 2021.•Benign hysterectomies performed in 2016 was 37.8% and increased to 45.2% in 2021.•Out of all benign hysterectomies performed during the study period, 23% were performed by GOs